Do bilinguals generalize estar more than monolinguals and what is the role of conceptual transfer?. (December 2019) - Adamou, Evangelia; De Pascale, Stefano; García-Márkina, Yekaterina; Padure, Cristian
Aims and objectives/purpose/research questions: Among the questions that remain open is whether bilingualism leads to simplification of alternatives in language in order to reduce cognitive load. This hypothesis has been supported by evidence showing that bilinguals generalize the Spanish copula estar 'to be' faster than monolinguals.﻿ Yet, other studies found no such clear trend. While conceptual transfer could account for the conflicting evidence in the literature, its role has not been demonstrated. Our study aims to fill this gap by testing simplification in Spanish copula choice among bilinguals and, in particular, the role of transfer. Design/methodology/approach: We used a contextualized copula choice task, comprising 28 sentences. Data and analysis: Sixty Romani–Spanish bilinguals from Mexico responded to the questionnaire in both Spanish and Romani. A control group of 62 Mexican Spanish monolinguals responded in Spanish. We constructed generalized linear mixed-effects models to analyse the results. Findings/conclusions: Analysis of the results reveals greater extension of estar among bilinguals for individual-level predicates as well as for traits not susceptible to change. Comparison of the responses of bilinguals (in Romani and in Spanish) and of Spanish monolinguals indicates that Romani could be reinforcing the generalization of estar in the Spanish responses of bilinguals. Originality: To our knowledge, this is the first study to examine copula choice in bilingual mode. In addition, it brings evidence from an under-researched community with little normative pressure. Significance/implications: Our study shows that conceptual transfer may be driving the extension of estar among bilinguals.